Board directors' foreign experience and firm dividend payouts - Tao, Qizhi; Wei, K.C. John; Xiang, Xueman; Yi, Biao (Journal of Corporate Finance, 2022)
We find that Chinese-listed firms are more likely to pay dividends and implement larger payout ratios when their directors have foreign experience. This finding remains after using various methods to address potential endogeneity concerns. The positive association is stronger for low-growth firms, non-state-owned firms, and when directors obtain foreign experience in countries with stronger investor protection. The effect of directors' foreign experience on dividend payouts is also more pronounced for independent directors than for executive directors. Directors with foreign experience appear to overcome the weak investor protection environment as the effects are more pronounced among poorly governed firms and before the regulatory dividend reforms in 2013. Overall, our findings identify a mechanism through which better governance practices are propagated.